2022
DOI: 10.54443/ijebas.v2i2.177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Current Ratio, Total Asset Turnover, Debt to Asset Ratio, and Debt to Equity Ratio on Return on Assets in Plantation Sub-Sector Companies Listed on the Indonesia Stock Exchange

Abstract: This study aims to analyze and apply the effect of the current ratio (CR), total asset turnover (TATO), debt to asset ratio (DAR), and debt to equity ratio (DER) on return on assets (ROA). The population in this study is plantation companies with 21 companies and a sample of 21 companies. The sampling technique used is a saturated sample/census; that is, all the population is sampled. The data collection technique uses documentation from financial reports published on the IDX's official website, namely www.IDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
1
1
Order By: Relevance
“…These empirical findings support research conducted by Alarussi and Alhaderi (2018), and Gunawan et al, (2022). However, it does not support the results of research from Sunjoko and Arilyn (2016) and Rajagukguk and Siagian (2021) which do not find any effect of operating asset turnover on company performance.…”
Section: ) Effect Of Operating Asset On Firm Performancecontrasting
confidence: 81%
See 2 more Smart Citations
“…These empirical findings support research conducted by Alarussi and Alhaderi (2018), and Gunawan et al, (2022). However, it does not support the results of research from Sunjoko and Arilyn (2016) and Rajagukguk and Siagian (2021) which do not find any effect of operating asset turnover on company performance.…”
Section: ) Effect Of Operating Asset On Firm Performancecontrasting
confidence: 81%
“…Sunjoko and Arilyn, (2016) who conducted research in Indonesia for the period 2007-2013, Nanda and Panda (2018) conducted in India, Nurlaela et al, (2019) who conducted research in Indonesia for the period , and Nguyen and Nguyen (2020 who conducted research in Vietnam found empirical evidence of a positive effect. While the results of research from Alarussi and Alhaderi (2018), Pervan et al, (2019), Rajagukguk and Siagian (2021), Bolarinwa et al, (2021), and Gunawan et al, (2022) did not find any effect of liquidity on company performance.…”
Section: Discussion 1) Effect Of Liquidity On Firm Performancementioning
confidence: 76%
See 1 more Smart Citation
“…A sample of industrial companies listed on the Iraq Stock Exchange was selected, as the sample size was (4) companies. The results of several studies (Githaiga, 2021) [18] , (Huang et al, 2021) [21] , (Gunawan et al, 2022, Bogan, 2012 [20,8] , (Denčić-Mihajlov et al, 2015) [11] showed that the financial structure. The dynamic positively affects the financial sustainability.…”
Section: Discussionmentioning
confidence: 98%
“…Analisa laporan keuangan bermanfaat dalam melihat dan memahami kekuatan dan kelemahan suatu koperasi (Gunawan et al, 2022). Laporan keuangan merupakan pernyataan situasi keuangan organiasi pada untuk periode waktu tertentu (Kasmir, 2016).…”
Section: Pendahuluanunclassified